Recovery of Platinum and Palladium from Scrap Automotive Catalytic Converters - Hammadi, Mohammed Qasim; Yassen, Rabiha Saleh; Abid, Kadhim Noori (Al-Khwarizmi Engineering Journal, 2017)
Abstract    The hydrometallurgical method was used to platinum and palladium leaching with aqua regia solution (3HCl: HNO3). The leaching experiments were designed to obtain the optimum conditions by using Taguchi method with 16 experiments at three different factors (time, temperature and solid to liquid ratio), and each factor has four different levels. In this study, leaching the powder sample of catalytic converter that contains platinum and palladium was conducted on the basis of the formation of chloro complexes platinum and palladium (PtCl62-, PdCl42-) with different concentrations in the acidic solution. The optimum conditions for leaching process are (time = 120 minutes, temperature = 100°C, and solid to liquid ratio = 1/20).The best efficiency for platinum and palladium leaching at these conditions were 97.58%, 93.23%, respectively. After leaching process at optimum conditions, platinum was firstly precipitated in the form of (NH4)2PtCl6 (ammonium chloroplatinate) by adding (5ml/l) of ammonium chloride (NH4Cl) as a precipitant agent .Then, palladium was precipitated in the form of (NH4)2PdClO3 (palladium ammonium chlorate) by adding (5g/l) of sodium chlorate (NaClO3) as a precipitant agent to the remaining solution after the removal of platinum. The best efficiency for platinum and palladium recovery at optimum leaching conditions were 91.94%, and 98.82%, respectively.                                                                                  Keywords: Aqua regia, catalytic converter, PGMs, Platinum, Palladium, recovery, catalytic converter, 3HCl:HNO3.